Components of Education: The Difference between Modern Education and the Islamic Perspective - Dr. Muhammad Ahmad; Dr. Muhammad Yaseen Raza; Dr. Mahmood Ahmad (Corresponding Author) (Journal of Religion and Society, 2025)
In terms of the reality of knowledge, secular and Islamic countries are on opposite ends of the spectrum. There are numerous famous names that define modern education, but we cannot include them all. One of the most well-known among them is John Dewey, who has had a significant impact on education throughout the previous century. His work is significant for portraying education in a secular context. John Dewey is concerned with preserving secular values. He founded his educational theories on the pragmatist philosophy. There is no such thing as limiting experience in modern education, and all material and social sciences will grow on this foundation. This is a significant contrast between the modern school system and the education system based on Islamic thinking. Many additional things can be manifestations of this foundation. This research paper provides a brief examination of the components of education, specifically the differences between modern education and the Islamic perspective. This page would serve as a doorway for researchers interested in studying the differences between Islamic and modern education systems. Keywords: Education system, Islamic Education, Modern Education, John Dewey